Association Between Carotid atherosclerosis And High Factor VIII Activity In Ischemic stroke (Bangladesh Journal of Neuroscience, 2014)
Background: A sample of 60 subjects from population based study participated in a study on carotid color duplex ultrasonography that aimed to assess the relations of coagulation factors to stroke and carotid atherosclerosis. The association between severity of carotid atherosclerosis and high factor viii activity in ischemic stroke is still not clear.Objective: The present study was conducted to find out the association between carotid atherosclerosis and high factor viii activity in ischemic stroke.Methodology: This was a cross sectional analytical study carried out in the department of neurology,BSMMU during the period of july’2009 to june’2011.A total 60 subjects with ischemic stroke were included in this study and data were collected purposively. Chi square test was done and probability value